Preeclampsia in pregnancy affecting the stemness and differentiation potency of haematopoietic stem cell of the umbilical cord blood - Nordin, Fazlina (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Umbilical cord blood (UCB) has been proposed as the potential source of haematopoietic stem cells (HSC) for allogeneic transplantation. However, few studies have shown that a common disease in pregnancy such as preeclampsia would affect the quality of UCB-HSC. Total nucleated cell count (TNC) is an important parameter that can be used to predict engraftment including UCB banking. Colony forming unit (CFU) assay is widely used as an indicator to predict the success of engraftment, since direct quantitative assay for HSC proliferation is unavailable. The aim of this study is to investigate the effects of preeclampsia in pregnancy on the stemness and differentiation potency of UCB-HSC. METHODS: Mononuclear cells (MNC) were isolated from UCB and further enriched for CD34+ cells using immune-magnetic method followed by CFU assay. A panel of HSC markers including differentiated haematopoietic markers were used to confirm the differentiation ability of UCB-HSC by flow cytometry analysis. RESULTS/ DISCUSSION: The HSC progenitor’s colonies from the preeclampsia group were significantly lower compared to the control. This correlates with the low UCB volume, TNC and CD34+ cells count. In addition, the UCB-enriched CD34+ population were lymphoid progenitors and capable to differentiate into natural killer cells and T-lymphocytes. CONCLUSION: These findings should be taken into consideration when selecting UCB from preeclamptic mothers for banking and predicting successful treatment related to UCB transplant.